KAJIAN TEORITIS TERHADAP TUGAS PEJABAT PEMBUAT AKTA TANAH DIKAITKAN DENGAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH DAN PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 TENTANG PERATURAN JABATAN PEJABAT PEMBUAT AKTA TANAH - HARUN PANDIA (SUPREMASI HUKUM, 2022)
Registration of land is a State obligation undertaken by the Head of the District Land Office/Cityassisted by PPAT, as mandated in Government Regulation number 24 of 1997 on Land Registrationand Government Regulation number 37 of 1998 on the Regulation of the Land Deed Officer Position.In this case I raised the issue of limiting factors in implementing the tasks PPAT associated withGovernment Regulation, as well as the implementation of the tasks PPAT in implementing landregistration data and guidance PPAT by Tangerang District Land Office. The method used is by usingempirical juridical approach to the specification of descriptive analytical research. Based on theresearch results can be given some conclusions that inhibiting factors in implementing the tasks PPATin supporting the maintenance activities of land registration data that there are still assignee is onlyintended to get a deed made by PPAT and is not intended to register their rights; so that the filesubmitted to the Land Office is not yet complete, and the result can not be implemented juridical datachanges. Keywords: Duty of PPAT, Land Registration Data